Penentuan Jumlah Konsumsi Dengan Metode Penalaran Fuzzy Mamdani (Studi Kasus Prediksi Konsumsi Susu Untuk Balita) - Agus Purwohandoko (Jurnal Ilmiah SINUS, 2010)
This paper is an explanation on fuzzy logic. Fuzzy logic has long been known and used in various fields by experts and engineers. The use of fuzzy logic was originally used for some fields, such as disease diagnosis system (in medicine); marketing system modeling, operations research (in economics); quality control, prediction of earthquakes, classification and pattern matching (in engineering).Mamdani Fuzzy logic method for the prediction of milk consumption is using Fuzzy Reasoning for testing multiple samples by several methods ranging from Centrolid, Bisector, MOM, SOM, LOM. Keywords : fuzzy logic, mamdani fuzz, MOM, SOM, LOM